2014
DOI: 10.1109/tnano.2013.2280648
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Range Hopping and Thermal Activation Conduction of Y-Doped ZnO Nanocrystalline Films

Abstract: ZnO and Y-doped ZnO nanocrystalline films were separately fabricated on the glass substrates by sol-gel spin-coating method. X-ray diffraction patterns of the films show the same wurtzite hexagonal structure and (002) preferential orientation. SEM images show that grain size and thickness of the nanocrystalline films decrease with increasing doping concentration. The decrease of optical bandgap with the increase of Y doping is deduced from the transmittance spectra. Temperature-dependent resistivity reveals a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…The E g values for pure and Y incorporated ZnO samples are a good agreement with values varied between 3.151 eV and 3.42 eV for Ga, In, Al and B doped ZnO samples [32,[36][37][38]. Unlike our results, Lin et al [25] found that E g value for pure ZnO dropped off from 3.2827 eV to 3.2656 eV with Y contribution in a sol-gel spin coating study. However, in another sol-gel dip coating study made by Yu et al [18], it was found that 0.5 at.% Y doping caused an increase in E g of pure ZnO from 3.30 eV to 3.37 eV and more Y doping brought about a decrease in the optical band gap.…”
Section: Optical Featuressupporting
confidence: 85%
See 2 more Smart Citations
“…The E g values for pure and Y incorporated ZnO samples are a good agreement with values varied between 3.151 eV and 3.42 eV for Ga, In, Al and B doped ZnO samples [32,[36][37][38]. Unlike our results, Lin et al [25] found that E g value for pure ZnO dropped off from 3.2827 eV to 3.2656 eV with Y contribution in a sol-gel spin coating study. However, in another sol-gel dip coating study made by Yu et al [18], it was found that 0.5 at.% Y doping caused an increase in E g of pure ZnO from 3.30 eV to 3.37 eV and more Y doping brought about a decrease in the optical band gap.…”
Section: Optical Featuressupporting
confidence: 85%
“…It is seen a shift to the small angles with Y doping. A shift to small angles with Y doping was also found by Lin et al [25] and Anandan and Muthukumaran [12]. The interplaner distance values (d) for each peak are determined with Bragg's law and interplaner distance values continuously increased with Y doping ratio.…”
Section: Crystallographic Featuressupporting
confidence: 68%
See 1 more Smart Citation
“…ln ( R ) vs. T −1 ) gives an excellent fit for our dataset with a reasonable barrier of 0.29 eV obtained from the slope of the fitting parameter, thus thermally activated conduction is a plausible mechanism. Note, the variable range hopping model for 3-dimensional conduction (in which ln ( σ ) is linearly proportional to T −1/4 , where σ is the conductivity) 30 31 fits also very well (not displayed here) to our data. However the extracted values for localization length as well as density of electronic states are unphysical thus this latter model for the conduction mechanism may be ruled out.…”
Section: Resultssupporting
confidence: 62%
“…For n -type semiconductors, the conduction process is mainly contributed by electrons that transition from the donor level to the conduction band. The relationship between resistivity ρ and temperature T can be expressed as [ 29 , 61 , 62 , 63 ] where ρ 0 is a constant, k B is the Boltzmann constant, and E a is the activation energy, which approximately measures the energy difference between the bottom of the conduction band and the donor level. The lower the activation energy, the easier it is for the donor electrons to jump to the conduction band.…”
Section: Resultsmentioning
confidence: 99%